Liposome-Encapsulated Hemoglobin Ameliorates Impairment of Fear Memory and Hippocampal Dysfunction After Cerebral Ischemia in Rats - Naobumi Hamadate (Journal of Pharmacological Sciences, 2010)
Abstract.: Liposome-encapsulated hemoglobin (LEH) has been developed as a blood substitute. In spite of its size (1/30 – 1/40 of erythrocytes), LEH has an oxygen-carrying capacity comparable to erythrocytes. Thus, LEH is expected to carry oxygen into vital organs via collateral routes during ischemia induced by vascular embolism. In the present study, we examined the therapeutic effects of LEH on behavioral impairments in rats after four-vessel occlusion (4VO) for 30 min. In the open-field test, locomotor activity in 4VO rats did not alter 7 days after ischemia. However, in the contextual fear conditioning (CFC) test, the freezing rate was significantly decreased in 4VO rats, although no behavioral changes in the Y-maze test and elevated plus-maze test were observed. Phosphorylation of the cyclic AMP response element-binding protein (CREB) in the hippocampal CA1 region after the CFC test was attenuated. These 4VO-induced impairments were significantly alleviated by the administration of LEH (5 ml/kg, i.v.) during occlusion. Moreover, LEH did not alter hippocampal blood flow and tissue oxygen pressure during 4VO, but it did suppress hyperoxia after ischemia–reperfusion. These findings suggest that LEH, an artificial oxygen carrier, could be a novel therapeutic agent for brain dysfunction after acute cerebral ischemia. Keywords:: artificial oxygen carrier, liposome-encapsulated hemoglobin, hippocampus, ischemia, contextual fear conditioning